Mad cow disease - Campbell, Peter N. (Acta Biologica Szegediensis, 2006)
The correct name for Mad Cow Disease is Bovine Spongiform Encephalopathy (BSE) and I will use this abbreviation throughout the text. BSE was first detected in England in 1985. Since then millions of cattle have been slaughtered either because they were infected or for precautionary measures. Payment for compensation to the farmers has cost the UK Government some Euro 6 billion. Although the UK has been the main site for BSE other countries have had BSE and all countries are forewarned. It seems certain that BSE has been transmitted to humans which has emphasised the necessity to protect the public from further infections. The many measures taken will be described. Basic research continues in an attempt to understand the science behind the advent of BSE but there remain many puzzling aspects. Some success has been achieved in identifying infected animals before the clinical symptoms appear. Naturally many professional people have been criticised for the spread of BSE and interesting lessons are being learnt from the links between politicians and scientists. There is little doubt that the standing of scientists in the public eye has been detrimentally affected by BSE.